ANALISA ANALISA KEPATUHAN WAJIB PAJAK BUMI DAN BANGUNAN (PBB) DI DESA PADAMUKTI TAHUN 2017 – 2020 - Satria Supriatna (EKBIS (Ekonomi & Bisnis), 2021)
Abstract Thiis study aims to determine (1) to determine the effect of motivation, fiscal services and tax sanctions through financial conditions on taxpayer compliance (2) land and building tax compliance in Padamukti village in 2017-2020, (4) obstacles in realizing mandatory compliance land and building tax in Padamukti village, and (5) how to overcome obstacles to compliance with land and building taxpayers in Padamukti village. This study uses a qualitative descriptive research design. Data were collected by documentation and interview methods. The data analysis technique used is descriptive qualitative. The results of the study show that (1) it is proven to be a motivation, tax authorities and tax sanctions through financial conditions have no significant effect on taxpayer compliance (2) tax compliance. Land and building tax compliance in Padamukti village in 2017-2020, namely 2017 (59% ), 2018 (58%), 2019 (53%) 2020 (53%). (3) The obstacles experienced in realizing the compliance of land and building taxpayers in Padamukti village are the lack of understanding and awareness of taxpayers, and the level of income of taxpayers. (4) The way to overcome obstacles in realizing taxpayer compliance and building is by providing socialization to taxpayers, and by checking tax rates. Keywords : tax compliance earth and building